ІЗ ІСТОРІЇ ІНСТИТУЦІЙ ВЕЛИКОБРИТАНІЇ: МІСЦЕ ТА РОЛЬ ТАЄМНОЇ РАДИ В СИСТЕМІ ДЕРЖАВНОГО УПРАВЛІННЯ АНГЛІЇ РАННЬОГО НОВОГО ЧАСУ (Zaporizhzhia Historical Review, 2021)
The article deals with the analysis of the development of the Privy Council in the structure of the state in England in the time of the early Tudors.The author presents changes in the Privy Council and the role of the Royal power in this process. The dynamics and character of interconnection of the Royal power and the Privy Council are displayed. Under the leadership of Privy Council some administrative reforms in the state governing of England of the first part of the XVI century were realized.